Application of charge transfer coated semiconductor material in gas sensitive sensing device

By applying charge transfer coated semiconductor materials in gas-sensitive sensors, the problems of low sensitivity, poor selectivity and high operating temperature in the prior art gas-sensitive sensors are solved, and gas detection with high sensitivity and selectivity at room temperature is realized. Simplifies the preparation process and reduces costs.

CN119147597AActive Publication Date: 2024-12-17FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411124241.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

Existing chemical resistance gas-sensitive sensors have problems such as low sensitivity, poor selectivity and high operating temperature, making it difficult to take into account stability, high sensitivity, fast response and room temperature detection.

Method used

Using charge transfer coated semiconductor material, organic components are closely coated on the initial semiconductor surface through charge transfer, improving carrier mobility and charge separation life, thereby improving gas detection sensitivity, and organically coated components The redox properties improve gas selectivity.

Benefits of technology

It realizes the improvement of the sensitivity and selectivity of gas detection at room temperature, reduces the working temperature, simplifies the material preparation process, reduces costs, and has stable material performance, which is suitable for a variety of gas detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147597A_ABST
    Figure CN119147597A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a charge transfer coated semiconductor material in a gas sensitive sensing device, and belongs to the technical field of semiconductor sensor materials. The application comprises the following steps: enabling the charge transfer coated semiconductor material to be in contact with gas to be detected; the charge transfer coated semiconductor material is a gas sensitive material formed by coating an organic component on the outer surface of an initial semiconductor through a charge transfer effect. According to the invention, the carrier mobility and the charge separation state life of the semiconductor are improved by utilizing the existence of charge transfer interaction, so that the gas detection sensitivity is improved, the working temperature is reduced, and the selectivity of the gas is improved by utilizing the redox characteristic of the organic coating component outside the semiconductor. The application of the invention not only retains the basic properties of the initial semiconductor, but also reduces the application cost by simplifying the material preparation mode, and has universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the application of a charge transfer coated semiconductor material in a gas sensitive sensor device, belonging to the technical field of semiconductor sensor materials. Background Art

[0002] Gas sensors can identify and sense the presence and concentration of specific gases in the working environment, and are widely used in detection in the fields of environment, public safety, food, etc. Chemiresistance gas sensors are sensors that convert the composition and concentration of detected gases into electrical signals. They have the characteristics of simple preparation process, low cost, easy integration, miniaturization, etc., and they occupy the mainstream of the current market. Gas-sensitive materials are the key components of chemiresistor gas sensors. At present, there are still a series of deficiencies: first, low room temperature sensitivity and high working temperature, that is, low sensitivity or no response at room temperature, usually requiring an operating temperature of more than 200°C, resulting in the need for a fixed socket for gas sensors, which is not conducive to on-demand layout, or shortening the service life of the supporting battery, causing maintenance troubles; second, poor selectivity, which is easily interfered by non-measured gases in the working environment, resulting in false alarms or failure to detect. In the prior art, the optimization methods of semiconductor gas-sensitive materials mainly include nano-sizing, doping, heterojunction construction, composite and heat treatment. These methods aim to improve the gas-sensitive properties of materials, such as sensitivity, selectivity and stability, by changing the structure, composition or surface properties of the materials. However, these methods are also accompanied by certain drawbacks: nano-technology can significantly increase the specific surface area of ​​materials and increase gas adsorption sites, but the agglomeration of nanoparticles may affect gas diffusion and adsorption, and the surface energy of nanomaterials is relatively high, which is easy to react with gases in the environment, resulting in decreased stability; doping technology changes the band structure and electron distribution of materials by introducing other elements, but excessive doping may lead to excessive conductivity, which in turn reduces gas sensing performance, and the introduction of doping elements may introduce new impurity phases, affecting the purity and stability of the material; heterojunction construction technology constructs heterojunctions of semiconductors and semiconductors, semiconductors and metals, or semiconductors and carbon materials (such as graphene, carbon nanotubes, etc.). The charge transfer and band bending at the heterojunction interface will affect the conductivity of gas-sensitive materials, thereby improving their gas sensing performance, but this technology is complex to prepare and has high cost; composite technology improves gas sensing performance by combining the advantages of multiple materials, but the preparation process of composite materials is complex, requiring precise control of the proportion and distribution of each component, and the interaction between the components may lead to unstable performance; heat treatment technology improves performance by improving the crystal structure and surface properties of materials, but high-temperature treatment may cause phase change or decomposition of materials, affecting stability and performance.

[0003] Therefore, it is very important to develop a simple and universal method to improve the sensitivity, selectivity and reduce the operating temperature of chemiresistive gas sensors. Summary of the invention

[0004] In order to solve the problems of low sensitivity, poor selectivity, high operating temperature and the difficulty in balancing many gas sensing properties (stability, high sensitivity, fast response and recovery, room temperature detection and good selectivity) existing in the prior art chemical resistance gas sensors, the present application provides an application of a charge transfer coated semiconductor material in a gas sensing device, and applies the charge transfer coated semiconductor material as a gas sensing material to the gas sensing device. The existence of charge transfer interaction is utilized to improve the carrier mobility and charge separation state lifetime of the semiconductor, thereby improving the gas detection sensitivity and reducing the operating temperature, and the redox characteristics of the organic coating component outside the semiconductor are utilized to improve the gas selectivity.

[0005] This application adopts the following technical solutions:

[0006] An application of a charge transfer coated semiconductor material in a gas sensing device comprises: contacting the charge transfer coated semiconductor material with a gas to be detected;

[0007] The charge transfer coated semiconductor material is:

[0008] A gas-sensitive material formed by organic components coating the outer surface of the initial semiconductor through charge transfer.

[0009] Optionally, the operating temperature of the gas sensor device is 0-200°C.

[0010] Optionally, the gas to be tested is an oxidizing gas and / or a reducing gas.

[0011] Optionally, the gas to be tested is selected from at least one of hydrogen sulfide, nitrogen dioxide, carbon monoxide, ammonia, sulfur dioxide, nitric oxide, and methane.

[0012] Optionally, the morphology of the initial semiconductor is selected from at least one of a microstructure or nanostructure, a thin film, and a bulk.

[0013] Optionally, the micro- or nanostructure is selected from at least one of a sheet-like, rod-like, spherical, and array structure of nano- or micro-size.

[0014] Optionally, the initial semiconductor is preferably in the form of a thin film.

[0015] Compared with bulk semiconductors, thin-film semiconductor materials have a higher specific surface area and more sites that can form charge transfer complexes with organic coating components, thereby improving the gas-sensing properties of semiconductor materials.

[0016] Optionally, the initial semiconductor is selected from at least one of an elemental semiconductor, a metal compound semiconductor, and an organic compound semiconductor.

[0017] Optionally, the elemental semiconductor is selected from at least one of silicon (Si), germanium (Ge), phosphorus (P), selenium (Se), antimony (Sb), and boron (B).

[0018] Optionally, the metal compound semiconductor is selected from at least one of metal oxides, sulfides, selenides, tellurides, phosphides, carbides, nitrides and halides.

[0019] Optionally, the metal oxide is selected from at least one of ZnO, TiO2, SnO2, WO3, Fe2O3, In2O3, CuO, Co3O4, Cr2O3, NiO, Mn3O4, and ZrO2.

[0020] Optionally, the sulfide is selected from at least one of ZnS, CdS, MoS2, and WS2.

[0021] Optionally, the organic compound semiconductor is selected from semiconductors such as coordination polymers, covalent organic frameworks COF, hydrogen bonded organic frameworks (HOF), and conductive polymers.

[0022] Optionally, the coordination polymer is selected from at least one of MOF-5, MOF-177, MOF-210, MOF-303, IRMOF series, UIO series, MIL series, and HTTP series.

[0023] Optionally, the covalent organic framework COF is selected from at least one of boron-containing COFs materials, imine-based COFs materials, triazine-based COFs materials, epoxy-based COFs materials, and anhydride-based COFs materials.

[0024] Preferably, the initial semiconductor is selected from at least one of TiO2, SnO2, UIO-66 semiconductor, and Cu-HTTP semiconductor.

[0025] Preferably, the initial semiconductor is in the form of a film or a powder.

[0026] Optionally, the organic component is selected from electron donating organic components and / or electron accepting organic components.

[0027] Optionally, the electron-donating organic component is selected from at least one of polythiophene (P3HT), polyphenylene vinylene (PPV) and its derivatives, polyaniline (PANI), polyfluorene (PF) and its derivatives, organic fullerene derivatives, polypyrrole, and polyparaphenylene vinylene.

[0028] Optionally, the electron-accepting organic component is selected from at least one of fullerene (C60), perylenetetracarboxylic acid diimide (NDI), perylenetetracarboxylic acid diimide (PDI), isoindigo (IC), methyl isoindigo (MeIC), viologen and its derivatives, 7,7,8,8-tetracyanoquinodimethane (TCNQ) and its derivatives, polythiadiazole, polyparaphenylene, polytriarylamine (PTAA) and its derivatives.

[0029] The above-mentioned organic component is a molecule which easily forms a charge transfer complex.

[0030] Preferably, the organic component is selected from at least one of single-terminal methyl viologen, double-terminal phenyl viologen, and 7,7,8,8-tetracyanoquinodimethane (TCNQ).

[0031] Optionally, the charge transfer coated semiconductor material is prepared by a method comprising the following steps:

[0032] S1, mixing materials containing the organic component and the solvent to obtain a coating solution;

[0033] S2, immersing the initial semiconductor in a coating solution and stirring or dispersing the initial semiconductor and a coating solution mixture to form a coating layer, and then washing and drying to obtain a charge transfer coated semiconductor material.

[0034] Optionally, the solvent is selected from at least one of water, ethanol, methanol, acetone, ethylene glycol, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0035] Optionally, the content of organic components in the charge transfer coated semiconductor material is 0.5-10%.

[0036] The applications include:

[0037] When the charge transfer coated semiconductor material is a double-terminal methyl viologen-coated TiO2 nanoarray or TiO2 nanopowder, the gas to be measured is H2S gas;

[0038] When the charge transfer coated semiconductor material is a SnO2 nanoarray or SnO2 nanopowder coated with double-terminal phenyl viologen, the gas to be measured is NO2 gas;

[0039] When the charge transfer coated semiconductor material is a double-terminal methyl viologen-coated ZnO nanoarray or ZnO nanopowder, the gas to be measured is H2S gas;

[0040] When the charge transfer coated semiconductor material is UIO-66 powder coated with 7,7,8,8-tetracyanoquinodimethane (TCNQ), the gas to be measured is CO gas;

[0041] When the charge transfer coated semiconductor material is Cu-HTTP powder coated with single-ended methyl viologen, the gas to be detected is NO gas.

[0042] When the charge transfer coated semiconductor material is ZnS powder coated with single-ended methyl viologen, the gas to be measured is NH3 gas.

[0043] When the charge transfer coated semiconductor material is MoS2 powder coated with single-ended methyl viologen, the gas to be measured is H2S gas.

[0044] When the charge transfer coated semiconductor material is P3HT powder coated with single-end ethyl viologen, the gas to be measured is CH4 gas.

[0045] When the charge transfer coated semiconductor material is COF-102 powder coated with double-terminal ethyl viologen, the gas to be measured is C2H2 gas.

[0046] When the charge transfer coated semiconductor material is Cu-HTTP powder coated with single-ended methyl viologen, the gas to be detected is NO gas.

[0047] The beneficial effects of this application include:

[0048] The application of the charge transfer coated semiconductor material provided in the present application in gas sensing devices, compared with the chemical resistance semiconductor material in the prior art, the present application adopts the charge transfer coated semiconductor material as the gas sensitive material, introduces organic matter into the initial semiconductor surface, and chemically coats the organic component tightly with the semiconductor through charge transfer interaction. This charge transfer interaction improves and takes into account many gas sensing properties of the initial semiconductor material (stability, sensitivity, response and recovery speed, operating temperature, selectivity). Compared with the semiconductor material optimization method in the prior art, the present application adopts the method of later introducing organic matter into the finished semiconductor material to form a charge transfer coated composite material, which retains the basic properties of the initial semiconductor and reduces the application cost by simplifying the material preparation method, and has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 shows the changes in the morphology and physical properties of the TiO2 nanoarray before and after coating in Preparation Example 1 of this application: (a) is a top-view electron microscope image of the TiO2 nanoarray (AA), (b) and (c) are top-view electron microscope images and cross-sectional images of the double-terminated methyl viologen-coated TiO2 nanoarray (AA@double-terminated methyl viologen). (d) is a schematic diagram of the color change of the TiO2 nanoarray film before and after charge transfer coating.

[0050] Figure 2This is the UV-visible diffuse reflectance image of the double-terminal methyl viologen-coated TiO2 nanoarray (AA@double-terminal methyl viologen) and the TiO2 nanoarray (AA) in Preparation Example 1 of this application.

[0051] FIG3 is a time chart showing the response of (a) the double-terminal methyl viologen-coated TiO2 nanoarray (AA@double-terminal methyl viologen) and (b) the TiO2 nanoarray (AA) to pure H2S gas at room temperature in Example 1 of the present application.

[0052] Figure 4 This is a comparison chart of the response percentages of the double-terminal methyl viologen-coated TiO2 nanoarray (AA@double-terminal methyl viologen) to H2S and interfering gases at room temperature in Example 1 of the present application.

[0053] Figure 5 This is a time diagram of the response of the double-terminal methyl viologen-coated TiO2 nanoarray (AA@double-terminal methyl viologen) and the TiO2 nanoarray (AA) to 10 ppm pure H2S gas at room temperature in Example 1 of the present application, demonstrating its stability. DETAILED DESCRIPTION

[0054] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0055] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0056] The double-terminated methyl viologen powder used in the embodiment was synthesized based on the method reported in the previous literature: 4,4'-bipyridine (8.0 g, 51.2 mmol) and chloroacetic acid (12.2 g, 129.1 mmol) were dissolved in 80 mL of acetonitrile and fully stirred and refluxed at 88°C for 36 hours. The reaction was closed, cooled to room temperature, and the solid product was collected by vacuum filtration and washed with hot acetonitrile, N,N'-dimethylacetamide and dichloromethane for 3-5 times until the sample color was washed to white. The collected product was placed in a vacuum oven at 80°C and vacuum dried to obtain a white powder product.

[0057] The synthesis process of the double-terminated phenyl viologen powder used in the embodiment follows the method reported in the previous literature: the whole synthesis process is divided into two key steps, the first step: first, 4,4'-bipyridine (12.0g, 76.8mmol) and 1-chloro-2,4-dinitrobenzene (51.6g, 254.4mmol) are dissolved in 200mL of acetonitrile, and the solution is stirred and refluxed for 60 hours at a constant temperature of 95°C. After the reaction is completed, it is cooled to room temperature and the solid product is collected by vacuum filtration. In order to remove residual impurities, the product is washed several times with hot acetonitrile, 3 to 5 times each time. Finally, the collected product is placed in a vacuum oven at 80°C for vacuum drying to remove residual moisture and solvent to obtain a pure white powdery first step product. Step 2: First, aniline (4575 μL, 50.2 mmol) was mixed with the product of the first step (13.5 g, 24.1 mmol), and then 100 mL of N, N'-dimethylacetamide was slowly added to it using a constant pressure dropping funnel. Stirring was maintained during the addition process to ensure that the two substances could be fully dissolved in N, N'-dimethylacetamide. Then, the resulting solution was stirred for 12 hours at a constant temperature of 93 ° C. After that, the temperature of the reaction system was lowered to 50 ° C, and 500 mL of ethyl acetate was added dropwise using a constant pressure dropping funnel. After the reaction was completed, the crude product was collected again by vacuum filtration, and the crude product was washed several times with hot N, N'-dimethylacetamide and ethyl acetate until the washing filtrate was colorless. In order to further improve the purity of the product, the powdered crude product was recrystallized in methanol. After removing the filter residue by filtration, the methanol solvent was removed using a vacuum rotary evaporator, and finally a reddish-brown crystalline double-terminated phenyl viologen product was obtained.

[0058] The TCNQ solid powder used in the examples was purchased from Adamas Company through commercial channels.

[0059] The TiO2 nanoarray film used in the example was prepared according to the literature (Document DOI: doi.org / 10.1002 / ange.202111519).

[0060] The SnO2 nanoarray film used in the example was prepared according to the literature (Document DOI: 10.1002 / solr.201800133).

[0061] The UIO-66 semiconductor powder used in the examples was purchased from Adamas Corporation through commercial channels.

[0062] The Cu-HTTP semiconductor powder used in the example was prepared according to the literature (Document DOI: doi.org / 10.1002 / ange.202212797).

[0063] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0064] The method of gas detection in the embodiment is: using the silver colloid double probe method, that is, a silver wire with a diameter of 50 microns is attached to the silver colloid as a conductive circuit. When preparing a chemical resistance sensor, this method is used to connect a pair of parallel electrodes at both ends of the film as the electrode part of the sensor. These sensors are then tested in a reported homemade sensing system. The sensor device is placed in an opaque sealed quartz chamber, and dry air is used as the carrier gas of the target gas at room temperature. In order to carry out gas-sensitive experiments, we monitored the changes in the direct current of the device under different concentrations of target gas. The measurement of the sensor device adopts a direct current circuit, and a bias voltage of 5V is applied, and the electrical performance test is carried out using a Keithley2602B semiconductor measuring instrument. The target gas is accurately controlled by a mass flow controller (CS-200C, produced by Beijing Qixing Mass Flow Electronic Equipment Manufacturing Co., Ltd.), and the qualified gas mixture from Beijing Huayuan Gas Chemical Co., Ltd., China is mixed with dry air in an appropriate proportion and introduced into a quartz tube. During the whole process, the gas flow rate remains constant at 200mL / min. All sensing measurements are carried out under standard environmental conditions. The above-mentioned gas detection method process can simultaneously obtain performance data such as the time, responsiveness, and stability of the gas sensor's response to gas.

[0065] The gases used in the test of gas responsiveness in this application include the following gases in the same concentration: hydrogen sulfide, nitrogen dioxide, nitric oxide, carbon monoxide, carbon dioxide, ammonia, methane, sulfur dioxide, sulfur trioxide, hydrogen, acetylene, ethylene, ethane, methanol, ethanol, acetone. In the specific test, the specific highly selective gas (test gas) corresponding to the charge transfer coated semiconductor material is one of the above gases, and other gases with low selectivity are called interfering gases.

[0066] The preparation of the charge transfer coated semiconductor material of the present application refers to the patent with publication number CN115672397A previously applied by the applicant.

[0067] According to one embodiment of the present application, the charge transfer coated semiconductor material is prepared by a method comprising the following steps: mixing materials containing the organic component and the solvent to obtain a coating solution; immersing and stirring the initial semiconductor in the coating solution to form a coating layer, and then washing and drying to obtain the charge transfer coated semiconductor material.

[0068] According to one embodiment of the present application, the charge transfer coated semiconductor material is prepared by a method comprising the following steps: mixing materials containing the organic component and the solvent to obtain a coating solution; dispersing the initial semiconductor and the coating solution mixture to form a coating layer, and then washing and drying to obtain the charge transfer coated semiconductor material.

[0069] This application uses the change in conductivity or resistivity of charge transfer coated semiconductor materials after contact with the gas to be measured for detection. In gas detection applications, the gas-sensitive material uses an organic component to coat the semiconductor and is combined with the semiconductor through a charge transfer interaction (i.e., there is a transfer of net charge between the two, thereby generating an electrostatic interaction), wherein the presence of the charge transfer interaction improves the carrier mobility and charge separation state life of the semiconductor, thereby improving the gas detection sensitivity and reducing the operating temperature. In addition, the redox characteristics of the organic coating component can improve the selectivity of the gas. Compared with the initial semiconductor, this type of material shows a significant improvement in gas-sensitive detection performance such as selectivity, stability, response speed, sensitivity, and operating temperature, and can detect gas at room temperature.

[0070] Preparation Example 1

[0071] The charge transfer coated semiconductor material was prepared by in-situ stirring-immersion synthesis method: 200 mg of double-terminal methyl viologen solid powder was completely dissolved in 20 ml of deionized water to prepare a double-terminal methyl viologen aqueous solution. A piece of TiO2 (initial semiconductor) nanoarray film was fixed with a clip, suspended in the double-terminal methyl viologen aqueous solution (not touching the bottom, not touching the stirring bar), and placed on a stirrer for 5 days of stirring. After the stirring, the TiO2 nanoarray film was removed and soaked in deionized water for 1 day to remove the unreacted double-terminal methyl viologen electron acceptor molecules. Finally, it was taken out from the deionized water and dried naturally to obtain a charge transfer coated semiconductor, that is, a TiO2 nanoarray coated with double-terminal methyl viologen, marked as AA@dimethyl viologen.

[0072] The morphological changes of TiO2 (initial semiconductor) nanoarrays before and after coating during the in-situ stirring-immersion synthesis process are shown in Figure 2. Figure 1a to Figure 1d As shown. The UV-visible diffuse reflectance spectra of TiO2 and AA@dimethylviologen were detected by Figure 2 It can be seen that the AA@dimethylviologen material has a wider light absorption range than the initial semiconductor. After the charge transfer complex is generated, the ultraviolet absorption edge can be clearly observed to be red-shifted, indicating the formation of the charge transfer complex.

[0073] Example 1

[0074] Take a piece of TiO2 nanoarray film (AA) and a piece of AA@dimethyl viologen obtained in Preparation Example 1 for gas sensing test:

[0075] First, air was introduced to remove impurities, and then pure H2S gas was introduced to test the changes in the electrical properties of the material. The test found that at room temperature (20-25°C), the response of the double-terminal methyl viologen-coated TiO2 nanoarray to H2S gas was 3000 times that of the TiO2 nanoarray at room temperature, indicating that the charge transfer coated semiconductor material produced a new adsorption reaction to the gas due to the organic matter coated on the surface. Figure 3a and Figure 3b The comparison shows that the AA@dimethyl viologen gas-sensitive material used in this application has excellent gas-sensitive adsorption and desorption capabilities. The comparison of the response percentage of AA@dimethyl viologen to H2S and interfering gas at room temperature is shown in the figure below. Figure 4 The response time of the double-terminal methyl viologen-coated TiO2 nanoarray (AA@double-terminal methyl viologen) and TiO2 nanoarray (AA) to 10ppm pure H2S gas at room temperature is shown in Figure 2, which indicates that AA@double-terminal methyl viologen has good selectivity for the gas to be tested. Figure 5 As shown, it can be seen that AA@ double-terminated methyl viologen has good stability.

[0076] Preparation Example 2

[0077] The charge transfer coated semiconductor material was prepared by the in-situ stirring-immersion synthesis method. The preparation method and conditions were the same as those in Preparation Example 1, except that the double-terminated methyl viologen solid powder was replaced by a double-terminated phenyl viologen solid powder, and the TiO2 (initial semiconductor) nanoarray film was replaced by a SnO2 nanoarray film to obtain a charge transfer coated semiconductor, i.e., a SnO2 nanoarray coated with a double-terminated phenyl viologen, marked as AA@double-terminated phenyl viologen.

[0078] Example 2

[0079] Take a piece of SnO2 nanoarray film and a piece of AA@biphenyl viologen obtained in Preparation Example 2 for gas sensing test:

[0080] Air is first introduced to remove impurities, and then pure NO2 gas is introduced to test the changes in the electrical properties of the material. The test found that at room temperature (20-25°C), the responsiveness of the SnO2 nanoarray coated with double-ended phenyl viologen to NO2 gas at room temperature is 500 times that of the SnO2 nanoarray, indicating that the charge transfer coated semiconductor material has a new adsorption reaction to the gas due to the surface coating of organic matter, and the gas-sensitive material provided in this application has excellent gas-sensitive adsorption and desorption capabilities. The results of testing the responsiveness of AA@double-ended phenyl viologen to NO2 and interfering gas at room temperature showed good selectivity for the gas to be tested, just like Example 1. The responsiveness of the SnO2 nanoarray (AA@double-ended phenyl viologen) and the TiO2 nanoarray (AA) coated with double-ended phenyl viologen to 10ppm pure NO2 gas at room temperature was tested. The results were similar to those in Example 1, and AA@double-ended methyl viologen also had good stability.

[0081] Preparation Example 3

[0082] The charge transfer coated semiconductor material was prepared by an in-situ stirring-immersion synthesis method: 200 mg of TCNQ solid powder was completely dissolved in 20 ml of ether to prepare a TCNQ ether solution, 3 mg of UIO-66 powder was immersed in the TCNQ ether solution, and placed on a stirrer for 3 days of stirring. After stirring, it was filtered, washed, centrifuged, and dried to remove unreacted TCNQ molecules to obtain a charge transfer coated semiconductor, i.e., TCNQ-coated UIO-66 powder, marked as UIO-66 semiconductor@TCNQ.

[0083] Example 3

[0084] 3 mg of UIO-66 powder and UIO-66 semiconductor @TCNQ powder obtained in Preparation Example 3 were taken for gas sensing tests:

[0085] Air is first introduced to remove impurities, and then pure CO gas is introduced to test the changes in the electrical properties of the material. The test found that at room temperature (20-25°C), the response of UIO-66 semiconductor @TCNQ powder to CO gas at room temperature is 1200 times that of UIO-66, indicating that the charge transfer coated semiconductor material has a new adsorption reaction to the gas due to the organic matter coated on the surface, and the gas-sensitive material provided in this application has excellent gas-sensitive adsorption and desorption capabilities. The response of UIO-66 semiconductor @TCNQ to CO and interfering gas at room temperature was tested, and the results showed good selectivity for the gas to be tested, just like Example 1. The response of TCNQ-coated UIO-66 powder (UIO-66 semiconductor @TCNQ) and UIO-66 powder to 10ppm pure CO gas at room temperature was tested. The results were similar to those in Example 1, and UIO-66 semiconductor @TCNQ also had good stability.

[0086] Preparation Example 4

[0087] The charge transfer coated semiconductor material was prepared by the in-situ stirring-immersion synthesis method. The preparation method and conditions were the same as those in Preparation Example 3, except that the TCNQ solid powder was replaced by the single-ended methyl viologen solid powder, and the UIO-66 powder was replaced by the Cu-HTTP powder to obtain a charge transfer coated semiconductor, i.e., Cu-HTTP powder coated with single-ended methyl viologen, marked as Cu-HTTP@single-ended methyl viologen.

[0088] Example 4

[0089] Take Cu-HTTP powder and a piece of Cu-HTTP@single-terminated methyl viologen powder obtained in Preparation Example 4 and perform gas sensing tests respectively:

[0090] Air was first introduced to remove impurities, and then pure NO gas was introduced to test the changes in the electrical properties of the material. The test found that at room temperature (20-25°C), the response of Cu-HTTP powder @ single-ended methyl viologen to NO gas at room temperature was 800 times that of Cu-HTTP powder, indicating that the charge transfer coated semiconductor material has a new adsorption reaction to the gas due to the surface coating of organic matter, and the gas-sensitive material provided in this application has excellent gas-sensitive adsorption and desorption capabilities. The response of Cu-HTTP@single-ended methyl viologen to NO and interfering gas at room temperature was tested, and the results showed good selectivity for the gas to be tested, just like in Example 1. The response of Cu-HTTP powder coated with single-ended methyl viologen (Cu-HTTP@single-ended methyl viologen) and Cu-HTTP powder to 10ppm pure NO gas at room temperature was tested. The results were similar to those in Example 1, and Cu-HTTP@single-ended methyl viologen also had good stability.

[0091] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. Application of a charge transfer coated semiconductor material in a gas sensor device, It is characterized in that include: contacting the charge transfer coated semiconductor material with the gas to be measured; The charge transfer coated semiconductor material is: A gas-sensitive material formed by organic components coating the outer surface of the initial semiconductor through charge transfer.

2. The use according to claim 1, It is characterized in that The working temperature of the gas sensor device is 0-200°C.

3. The use according to claim 1, It is characterized in that The gas to be tested is an oxidizing gas and / or a reducing gas; Preferably, the gas to be measured is selected from at least one of hydrogen sulfide, nitrogen dioxide, carbon monoxide, ammonia, sulfur dioxide, nitric oxide and methane.

4. The use according to claim 1, It is characterized in that The morphology of the initial semiconductor is selected from at least one of a micro- or nano-structure, a thin film, and a bulk; The micron or nano structure is selected from at least one of a sheet-like, rod-like, spherical, and array structure of nanometer or micron size.

5. The use according to claim 1, It is characterized in that The initial semiconductor is selected from at least one of an element semiconductor, a metal compound semiconductor, and an organic compound semiconductor.

6. The use according to claim 5, It is characterized in that The elemental semiconductor is selected from at least one of silicon, germanium, phosphorus, selenium, antimony and boron; Preferably, the metal compound semiconductor is selected from at least one of metal oxides, sulfides, selenides, tellurides, phosphides, carbides, nitrides, and halides; Preferably, the metal oxide is selected from ZnO, TiO 2 SnO 2 , WO 3 , Fe 2 O 3 、In 2 O 3 ,CuO,Co 3 O 4 Cr 2 O 3 、NiO、Mn 3 O 4 、ZrO 2 At least one of; Preferably, the sulfide is selected from ZnS, CdS, MoS 2 , WS 2 At least one of; Preferably, the organic compound semiconductor is selected from semiconductors such as coordination polymers, covalent organic frameworks COFs, hydrogen bonded organic frameworks, and conductive polymers; Preferably, the coordination polymer is selected from at least one of MOF-5, MOF-177, MOF-210, MOF-303, IRMOF series, UIO series, MIL series, and HTTP series; Preferably, the covalent organic framework COF is selected from at least one of boron-containing COFs materials, imine-based COFs materials, triazine-based COFs materials, epoxy-based COFs materials, and anhydride-based COFs materials.

7. The use according to claim 1, It is characterized in that The organic component is selected from electron-donating organic components and / or electron-accepting organic components; Preferably, the electron-donating organic component is selected from at least one of polythiophene, polyphenylene vinylene and its derivatives, polyaniline, polyfluorene and its derivatives, organic fullerene derivatives, polypyrrole, and polyparaphenylene vinylene; Preferably, the electron-accepting organic component is selected from at least one of fullerene, perylenetetracarboxylic acid diimide, perylenetetracarboxylic acid diimide, isoindigo, methyl isoindigo, viologen and its derivatives, 7,7,8,8-tetracyanoquinodimethane and its derivatives, polythiadiazole, polyparaphenylene, polytriarylamine and its derivatives.

8. The use according to claim 1, It is characterized in that The charge transfer coated semiconductor material is prepared by a method comprising the following steps: S1, mixing materials containing the organic component and the solvent to obtain a coating solution; S2, immersing the initial semiconductor in a coating solution and stirring or dispersing the initial semiconductor and a coating solution mixture to form a coating layer, and then washing and drying to obtain a charge transfer coated semiconductor material.

9. The use according to claim 8, It is characterized in that The solvent is selected from at least one of water, ethanol, methanol, acetone, ethylene glycol, N,N-dimethylformamide and N,N-dimethylacetamide.

10. The use according to claim 8, It is characterized in that The content of organic components in the charge transfer coated semiconductor material is 0.5-10%.

Citation Information

Patent Citations

  • Organic semiconductor gas sensor with organic heterojunction-containing gas-sensitive layer

    CN102692445A

  • Application of one-dimensional ordered tungsten oxide / titanium oxide core-shell nanowire in detecting nitrogen dioxide

    CN107402240A

  • Room-temperature NO2 sensor based on graphene-coated alpha-Fe2O3 compound and preparation method thereof

    CN107966480A

  • High-selectivity hydrogen sensor supported sensitive material as well as preparation method and application thereof

    CN114910523A

  • Organic coated composite semiconductor material and preparation method and application thereof

    CN115672397A

Cited By

  • Humidity sensor based on hydrogen bond organic framework material and preparation method

    CN119936135A